2(3z-1)-2(4-2Z)=8

Simple and best practice solution for 2(3z-1)-2(4-2Z)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3z-1)-2(4-2Z)=8 equation:


Simplifying
2(3z + -1) + -2(4 + -2Z) = 8

Reorder the terms:
2(-1 + 3z) + -2(4 + -2Z) = 8
(-1 * 2 + 3z * 2) + -2(4 + -2Z) = 8
(-2 + 6z) + -2(4 + -2Z) = 8
-2 + 6z + (4 * -2 + -2Z * -2) = 8
-2 + 6z + (-8 + 4Z) = 8

Reorder the terms:
-2 + -8 + 4Z + 6z = 8

Combine like terms: -2 + -8 = -10
-10 + 4Z + 6z = 8

Solving
-10 + 4Z + 6z = 8

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 4Z + 10 + 6z = 8 + 10

Reorder the terms:
-10 + 10 + 4Z + 6z = 8 + 10

Combine like terms: -10 + 10 = 0
0 + 4Z + 6z = 8 + 10
4Z + 6z = 8 + 10

Combine like terms: 8 + 10 = 18
4Z + 6z = 18

Add '-6z' to each side of the equation.
4Z + 6z + -6z = 18 + -6z

Combine like terms: 6z + -6z = 0
4Z + 0 = 18 + -6z
4Z = 18 + -6z

Divide each side by '4'.
Z = 4.5 + -1.5z

Simplifying
Z = 4.5 + -1.5z

See similar equations:

| 13x-7=12x-12+x+5 | | -3/2y=22 | | 75-9n= | | p/14=1 | | -20=k-19 | | 10x-16=8x+7 | | -54=9h | | 4b+2=9b-23 | | 0.28y+8=11 | | 3(6x-5)=18x+15x | | b/17=-13 | | 4(x-30)+5x=-48 | | x+(1+x)+(2+x)=228 | | 5r-4r=16 | | -8(9h-5)=-17 | | -12+4n=4 | | -11+b=-3 | | 19a-12-4a=(-57) | | (Y6/Y3)4 | | k/18=-4 | | 393=17n+2 | | 13=11-y | | m/15=16 | | -6x-10=-16 | | -5d-24=4(1d+6)-1d | | 6x+21=6x+24-3 | | 2(2z-3)-2(4-5z)=2 | | -50x^10/10x^5 | | -5-3x=25 | | 2m-8=6 | | 3a^2+10=0 | | 5x(x-3)+6=5x-9 |

Equations solver categories